Discovered in historical collections: Two new Japalura species (Squamata: Sauria: Agamidae) from Yulong Snow Mountains, Lijiang Prefecture, Yunnan, PR China - Manthey, Ulrich; Denzer, Wolfgang; Hou, Mian; Wang, Xiaohe (Zootaxa, 2012)
Several specimens from historical collections made in Yunnan (PR China) were found to be inconsistent with hithertoknown species of Japalura. Two species are described as new: Japalura brevicauda spec. nov. and Japalura yulongensisspec. nov. Diagnostic features for the new species are compiled and a key to closely related species is produced. The geographical distribution of these species is outlined and discussed.